Left-sided mini-maze procedure via the left atrial appendage. (26th February 2014) - Ismail, Issam; Fleissner, Felix; Cebotari, Serghei; Rustum, Saad; Haverich, Axel
Abstract: This study presents a novel way to perform the mini-maze procedure through the left atrial appendage. By this way, the usual additional incision of the intra-atrial groove is avoided, especially in patients receiving coronary artery bypass grafting (CABG) or aortic valve replacement without mitral valve disease. We retrospectively analysed 23 consecutive patients who received this novel mini-maze procedure between 2009 and 2011. In recognition of a learning curve, we divided the patients into two groups (Group 1: Patients 1–11 versus Group 2: Patients 12–23), according to the date of operation. In Group 2, 7 patients (58.33%) were completely free of atrial fibrillation at the time of the follow-up. In Group 1, only 2 (18.18%) patients were successfully treated resulting in a stable sinus rhythm at the time of the follow-up. The mini-maze procedure performed through the left atrial appendage is a safe and feasible technique; however, it seems to be less effective than the Cox-maze III procedure and is associated with a learning curve.